Persepsi mahasiswa terhadap pemberian kuis interaktif dalam proses pembelajaran pada mahasiswa Program Studi Pendidikan Dokter Universitas Lampung: Sebuah studi kualitatif - Putri, Lulu Rafika; Saputra, Oktadoni; Wijaya, Sofyan Musyabiq (CV. Jasa Sukses Abadi, 2023)
The condition of the COVID-19 pandemic affects many aspects of education, one of which is the increased use of electronic or digital media as a means that can support the learning process. The selection of appropriate and interesting teaching and learning media is important to support the learning process. This study aims to explore student perceptions of the provision of interactive quizzes in the learning process for students of the University of Lampung Medical Education Study Program: A Qualitative Study. This study used a qualitative research design with a phenomenological approach. The informants in this study were first, second, third, and fourth year students with six informants who met the criteria of gender and Grade Point Average (GPA), as well as four lecturers. Data were collected through Focus Group Discussion (FGD) with medical students and in-depth interviews with lecturers. Data were analyzed using thematic analysis. There are various perceptions from students regarding the provision of interactive quizzes in the learning process. The perceptions obtained are related to the advantages, disadvantages and effectiveness of providing interactive quizzes in the learning process.